LITERATURE REVIEW: THE RELATIONSHIP BETWEEN SMARTPHONE USE AND INCIDENTS OF ANXIETY (NOMOPHOBIA) AMONG ADOLESCENTS IN INDONESIA - Silmi, Ayun Zul; Lailiyah, Syifa’ul (Journal of Community Mental Health and Public Policy, 2024)
Background: Smartphones were an information and communication technology that could not be separated from human life. High-intensity use of smartphones led to addiction. Dependence on smartphones could lead to anxiety disorders or so-called nomophobia. Purpose: To determine the relationship between smartphone, use and the incidence of anxiety (nomophobia) in adolescents in Indonesia. Methods: The literature review used national articles published in 2019-2024. Articles were searched using the Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) method. Inclusion criteria include articles with quantitative research, as well as mixed methods with research subjects on adolescents in Indonesia. A total of eleven articles were included. This research used national standard articles with an article search database, namely Google Scholar and Garuda. Results: Based on the eleven articles analysed, there is a relationship between anxiety disorders (nomophobia) in adolescents in Indonesia and the intensity of their use. Conclusion: The high use of smartphones is associated with a higher tendency of nomophobia. High intensity of smartphone use is influenced by several factors, including various interesting features of smartphones, one of which is social media, the COVID-19 pandemic, and the feeling of not wanting to be left behind by trends among teenagers. Abstrak Latar belakang: Smartphone merupakan salah satu teknologi informasi dan komunikasi yang tidak bisa terlepas dari kehidupan manusia. Penggunaan smartphone dengan intensitas tinggi menyebabkan ketergantungan. Ketergantungan pada smartphone dapat menyebabkan timbulnya gangguan kecemasan atau yang disebut Nomophobia. Tujuan: Untuk mengetahui hubungan penggunaan smartphone terhadap kejadian kecemasan (Nomophobia) pada remaja di Indonesia. Metode: Penelitian studi literatur menggunakan artikel nasional tahun terbit 2019-2024. Pencarian artikel dilakukan menggunakan metode Preferred Reporting Items for Systematic Review & Meta-Analyses (PRISMA). Kriteria inklusi meliputi artikel dengan penelitian kuantitatif, serta mix methods dengan subjek penelitian pada remaja di Indonesia. Sebanyak sebelas artikel yang masuk kedalam kriteria. Penelitian ini menggunakan artikel berstandar nasional dengan database pencarian artikel yaitu Google Scholar dan Garuda. Hasil: Berdasarkan sebelas artikel yang dianalisis, terdapat hubungan antara gangguan kecemasan (Nomophobia) pada remaja di Indonesia dengan intensitas penggunaannya. Kesimpulan: Tingginya penggunaan smartphone dipengaruhi oleh beberapa faktor, antara lain macam-macam fitur yang menarik pada smartphone salah satunya yaitu media sosial, adanya pandemi COVID-19, dan perasaan tidak ingin ketinggalan tren di kalangan remaja.